INTERPERSONAL MEANING ANALYSIS OF ADELE’S SONG LYRIC IN 21 ALBUM - Hernovianti Puspa Sari; Neng Rini Dartini; Euis Rina Mulyani (PROJECT (Professional Journal of English Education), 2019)
Songs are one of media in language to communicate or deliver a message which created by a songs’ writer through a singer to listeners. Songs is very effective as a media in analyzing systemic functional linguistic, because in song contained two text at once, those are when a singers sing, the song is the spoken text, and the song lyric is the written text. The objective of this study is to describe the aspects of Interpersonal Meaning in the lyric of Adele’s Album 21. The design of the research was descriptive qualitative method. The writers analyzed the a song entitled ”Don’t You Remember” based on the Subject, Finite, Predicator, Complement and Adjunct that describe in the table. The writers classified them based on Mood-Residue elements and made the conclusion based on the research findings. The results of the data analysis shows that the interpersonal meaning in the lyric Don’t You Remember of Adele’s album “21”, there are only 4 clauses which do not have aspects of interpersonal meaning from 28 clauses which be analyzed because the clauses only have one element, it is residue. Thus, the conclusion is  85.7 % of the data can be analyzed to find out mood and residue  as the aspects of interpersonal meaning.Keywords: Interpersonal meaning, Song lyric